Ultra-high temperature ceramic-based aerogel composite material and preparation method thereof

By using a combination of polybenzoxazine, mullite fiber and ZrO2, a sol-gel process and ultra-high temperature calcining process, a ceramic-based aerogel composite material was prepared, solving the problem of insufficient mechanical strength and thermal insulation performance of existing materials, and achieving significant improvement in material performance and reduction of preparation costs.

CN119735447APending Publication Date: 2025-04-01吉祥三宝高科新材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411917276.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing ceramic-based aerogel materials have shortcomings in terms of mechanical strength and thermal insulation properties, and the preparation method is complex and costly.

Method used

Polybenzoxazine, mullite fiber and ZrO2 are used as the main raw materials, and ceramic-based aerogel composite materials are prepared through sol-gel process and ultra-high temperature calcination process. The method includes crosslinking benzoxazine with mullite fibers to form aerogel composite precursor, and impregnating by ZrC xylene solution and ultra-high temperature calcining to form a tightly fit ZrO2 layer, improving the thermal insulation and mechanical properties of the material.

Benefits of technology

It significantly improves the mechanical properties and thermal insulation properties of ceramic-based aerogel composites, reduces the preparation cost, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207104730000071
    Figure BDA0005207104730000071
  • Figure BDA0005207104730000081
    Figure BDA0005207104730000081
Patent Text Reader

Abstract

The invention discloses an ultra-high temperature ceramic-based aerogel composite material and a preparation method thereof, and belongs to the technical field of composite materials. A preparation method of an ultra-high temperature ceramic-based aerogel composite material comprises the following steps: S1. After mixing benzoxazine, 4,4'-diaminodiphenylmethane and N,N-dimethylformamide, oxalic acid DMF solution is added, and stirred for 1-2 hours to obtain a slurry; S2. After mixing a polyvinyl alcohol aqueous solution and a hydrogen peroxide aqueous solution, slowly dropwise add them to the above slurry, stir for 8-10 hours, and obtain a sol; S3. Impregnate mullite fiber into the sol under vacuum conditions, solidify, and obtain a ceramic-based aerogel composite material precursor; S4. Impregnate the aerogel composite material precursor into a mixed solution of ZrC and xylene under vacuum conditions, seal and stand, dry, calcine, and cool to room temperature to obtain a ceramic-based aerogel composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and in particular relates to an ultra-high temperature ceramic-based aerogel composite material and a preparation method thereof. Background Art

[0002] Ceramic-based aerogels are a unique class of porous materials that combine the advantages of ceramics and aerogels. In recent years, these materials have attracted widespread attention due to their excellent properties and wide range of applications. Ceramic-based aerogels are derived from inorganic precursors and formed by methods such as sol-gel processes, and then maintained in their nanostructured porous networks by supercritical drying or other drying techniques. The resulting material is a highly porous, low-density and lightweight ceramic with a three-dimensional network structure containing interconnected pores.

[0003] Compared with traditional ceramics, ceramic fiber aerogel has the following advantages: 1. High porosity and large specific surface area; 2. Adjustable pore size; 3. Low density and light weight; 4. High thermal stability and thermal shock resistance; 5. Mechanical strength; 6. Chemical stability and corrosion resistance; However, there are the following problems when using the commonly used sol-gel synthesis: 1. Purity problem, the sol-gel method may introduce impurities (such as residual solvents or catalysts) into the final aerogel material; 2. Slow gelation, the sol-gel process sometimes involves a slow gelation time; 3. Limited mechanical strength, due to its highly porous structure, ceramic aerogels synthesized using the sol-gel method may exhibit limited mechanical strength.

[0004] The patent application with publication number CN 104261797 A discloses a method for preparing a glass fiber reinforced TiO2-SiO2 composite aerogel thermal insulation material. The material is prepared by using alkaline silica sol and TiO2 powder as raw materials, impregnating glass fiber felt, undergoing a first ethanol solvent replacement, silane surface modification, and a second ethanol solvent replacement, and finally undergoing ethanol supercritical drying or carbon dioxide supercritical drying. The thermal conductivity of the material is low, and the thermal conductivity at 600°C is 0.031-0.045 W / m·K. However, the preparation method is relatively complicated and the cost is relatively high. In addition, the composite aerogel thermal insulation material still has room for improvement in terms of thermal insulation and mechanical strength. Therefore, how to prepare a ceramic and aerogel composite material with high mechanical strength and strong thermal insulation to make it more widely applicable is an extremely concerning issue. Summary of the invention

[0005] The object of the present invention is to provide an ultra-high temperature ceramic-based aerogel composite material and a preparation method thereof, so as to improve the mechanical properties of the ceramic-based aerogel composite material.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] An ultra-high temperature ceramic-based aerogel composite material comprising polybenzoxazine, mullite fiber and ZrO2;

[0008] The polybenzoxazine and mullite fibers are cross-linked to obtain a ceramic-based aerogel composite material precursor;

[0009] The ZrO2 is coated on the outer layer of the ceramic-based aerogel composite material precursor.

[0010] A method for preparing an ultra-high temperature ceramic-based aerogel composite material comprises the following steps:

[0011] S1. After mixing benzoxazine, 4,4'-diaminodiphenylmethane and N,N-dimethylformamide, add oxalic acid DMF solution and stir for 1-2h to obtain a slurry;

[0012] S2. After mixing the aqueous solution of polyvinyl alcohol and the aqueous solution of hydrogen peroxide, slowly dropwise add the mixture to the slurry and stir for 8-10 hours to obtain a sol;

[0013] S3. impregnating the mullite fiber into the sol under vacuum conditions and curing to obtain a ceramic-based aerogel composite material precursor;

[0014] S4. The aerogel composite material precursor is immersed in a mixed solution of ZrC and xylene under vacuum conditions, sealed and allowed to stand, dried, calcined, and cooled to room temperature to obtain a ceramic-based aerogel composite material.

[0015] Furthermore, the oxalic acid concentration in the oxalic acid DMF solution is 7.15 mol / L, and the density of the mullite fiber is 0.15-0.2 g / cm 3 .

[0016] Furthermore, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 2%-3%; the mass fraction of hydrogen peroxide in the hydrogen peroxide aqueous solution is 30%-35%.

[0017] Furthermore, the mass fraction of ZrC in the mixed solution of ZrC and xylene is 2%-5%.

[0018] Furthermore, the usage ratio of the benzoxazine, 4,4'-diaminodiphenylmethane, oxalic acid DMF solution, N,N-dimethylformamide, polyvinyl alcohol aqueous solution and hydrogen peroxide aqueous solution is 3-5 g: 1-2 g: 18-21 mL: 25-35 mL: 4-6 mL: 2-4 mL.

[0019] Furthermore, the curing is performed in an inert gas atmosphere at 150-200° C. for 2-3 hours.

[0020] Furthermore, the immersion time is 0.5-1h; the sealing and standing time is 3-4d.

[0021] Furthermore, the drying is performed at 55-65° C. for 22-24 hours; and the calcination is performed by heating the mixture to 1050-1150° C. at a heating rate of 5-10° C. / min and maintaining the temperature for 1.5-2.5 hours.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention provides an ultra-high temperature ceramic-based aerogel composite material, which combines the advantages of ceramic fiber and aerogel. Benzoxazine has inherent flame retardancy and heat resistance due to its rich benzene rings and nitrogen atoms in its structure; mullite fiber serves as a framework to enhance the mechanical properties of the composite material, and the inherent characteristics of ZrO2 enhance the thermal insulation performance and thermal stability of the composite material.

[0024] (2) The preparation method adopted by the present invention first polymerizes benzoxazine and then fills the pores between fibers and adheres to the fiber surface to obtain a stable composite material precursor. The hydrogen peroxide aqueous solution generates gas during the reaction to produce a porous structure in the composite material. The ZrC xylene solution enters the pores by immersion and is in situ ceramicized into ZrO2 under ultra-high temperature calcination. The ZrO2 is tightly attached to the ceramic-based aerogel composite material precursor, which greatly improves the thermal insulation performance of the material and solves the problem of uneven dispersion of ZrO2 in the material. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] This embodiment provides an ultra-high temperature ceramic-based aerogel composite material, which is prepared by the following steps:

[0028] S1. After mixing 4 g of benzoxazine, 1.5 g of 4,4'-diaminodiphenylmethane and 30 mL of N,N-dimethylformamide, 20 mL of 7.15 mol / L oxalic acid DMF solution was added and stirred for 1.5 h to obtain a slurry;

[0029] S2. 5 mL of a 3% aqueous solution of polyvinyl alcohol and 3 mL of a 35% aqueous solution of hydrogen peroxide were mixed and slowly added dropwise to the slurry and stirred for 9 h to obtain a sol;

[0030] S3. The density is 0.18g / cm 3 The mullite fiber was impregnated into the sol under vacuum conditions for 1 hour, and then cured in an inert gas atmosphere at 180°C for 2.5 hours to obtain a ceramic-based aerogel composite material precursor.

[0031] S4. The aerogel composite material precursor is immersed in a 3% by mass ZrC xylene mixture under vacuum conditions for 1 hour, sealed and allowed to stand for 3 days, dried at 60°C for 24 hours, heated to 1100°C at a heating rate of 8°C / min and kept warm for 2 hours, and cooled to room temperature to obtain a ceramic-based aerogel composite material.

[0032] Example 2

[0033] The present embodiment is different from the embodiment 1 in that the “4 g benzoxazine, 1.5 g 4,4'-diaminodiphenylmethane” in S1 is changed to “3 g benzoxazine, 2 g 4,4'-diaminodiphenylmethane”.

[0034] The remaining raw materials and preparation process remain the same as in Example 1.

[0035] Example 3

[0036] The present embodiment is different from the embodiment 1 in that the “4 g benzoxazine, 1.5 g 4,4'-diaminodiphenylmethane” in S1 is changed to “5 g benzoxazine, 1 g 4,4'-diaminodiphenylmethane”.

[0037] The remaining raw materials and preparation process remain the same as in Example 1.

[0038] Example 4

[0039] The present embodiment is different from the embodiment 1 in that the “5 mL of 3% polyvinyl alcohol aqueous solution and 3 mL of 35% hydrogen peroxide aqueous solution” in S2 is changed to “6 mL of 3% polyvinyl alcohol aqueous solution and 2 mL of 35% hydrogen peroxide aqueous solution”.

[0040] The remaining raw materials and preparation process remain the same as in Example 1.

[0041] Example 5

[0042] Compared with Example 1, the present embodiment is different in that "5 mL of 3% polyvinyl alcohol aqueous solution and 3 mL of 35% hydrogen peroxide aqueous solution" in S2 is changed to "4 mL of 3% polyvinyl alcohol aqueous solution and 4 mL of 35% hydrogen peroxide aqueous solution".

[0043] The remaining raw materials and preparation process remain the same as in Example 1.

[0044] Comparative Example 1

[0045] Compared with Example 1, this comparative example differs in that the impregnation step in S4 is not performed, and the specific implementation steps are as follows:

[0046] S1. After mixing 4 g of benzoxazine, 1.5 g of 4,4'-diaminodiphenylmethane and 30 mL of N,N-dimethylformamide, 20 mL of 7.15 mol / L oxalic acid DMF solution was added and stirred for 1.5 h to obtain a slurry;

[0047] S2. 5 mL of a 3% aqueous solution of polyvinyl alcohol and 3 mL of a 35% aqueous solution of hydrogen peroxide were mixed and slowly added dropwise to the slurry and stirred for 9 h to obtain a sol;

[0048] S3. The density is 0.18g / cm 3 The mullite fiber was impregnated into the sol under vacuum conditions for 1 hour, and cured in an inert gas atmosphere at 180°C for 2.5 hours to obtain a ceramic-based aerogel composite material precursor; the mixture was sealed and allowed to stand for 3 days, dried at 60°C for 24 hours, heated to 1100°C at a heating rate of 8°C / min and kept warm for 2 hours, and then cooled to room temperature to obtain a ceramic-based aerogel composite material.

[0049] The remaining raw materials and preparation process remain the same as in Example 1.

[0050] Comparative Example 2

[0051] Compared with Example 1, this comparative example differs in that no mullite fiber is added, and the specific implementation steps are as follows:

[0052] S1. After mixing 4 g of benzoxazine, 1.5 g of 4,4'-diaminodiphenylmethane and 30 mL of N,N-dimethylformamide, 20 mL of 7.15 mol / L oxalic acid DMF solution was added and stirred for 1.5 h to obtain a slurry;

[0053] S2. 5 mL of a 3% aqueous solution of polyvinyl alcohol and 3 mL of a 35% aqueous solution of hydrogen peroxide were mixed and slowly added dropwise to the slurry and stirred for 9 h to obtain a sol;

[0054] S3. Add 15 mL of a 3% ZrC xylene mixture into the sol, immerse for 1 hour, and cure in an inert gas atmosphere at 180°C for 2.5 hours to obtain a ceramic-based aerogel composite material precursor; seal and let stand for 3 days, dry at 60°C for 24 hours, heat to 1100°C at a heating rate of 8°C / min and keep warm for 2 hours, and then cool to room temperature to obtain a ceramic-based aerogel composite material.

[0055] The remaining raw materials and preparation process remain the same as in Example 1.

[0056] Comparative Example 3

[0057] Compared with Example 1, this comparative example differs in that "benzoxazine sol" is replaced with "water glass sol", and the specific implementation steps are as follows:

[0058] S1. Adding water glass solution to phosphoric acid (wherein the volume ratio of phosphoric acid to water glass solution is 1:15-25; the water glass solution is diluted by water glass and deionized water in a volume ratio of 1:2-4) to obtain a slurry;

[0059] S2. 5 mL of a 3% aqueous solution of polyvinyl alcohol and 3 mL of a 35% aqueous solution of hydrogen peroxide were mixed and slowly added dropwise to the slurry, stirred for 9 h, and sealed and aged to obtain a water glass sol;

[0060] S3. The density is 0.18g / cm 3 The mullite fiber was impregnated into the sol under vacuum conditions for 1 hour, and then cured in an inert gas atmosphere at 180°C for 2.5 hours to obtain a ceramic-based aerogel composite material precursor.

[0061] S4. The aerogel composite material precursor is immersed in a 3% by mass ZrC xylene mixture under vacuum conditions for 1 hour, sealed and allowed to stand for 3 days, dried at 60°C for 24 hours, heated to 1100°C at a heating rate of 8°C / min and kept warm for 2 hours, and cooled to room temperature to obtain a ceramic-based aerogel composite material.

[0062] The remaining raw materials and preparation process remain the same as in Example 1.

[0063] Comparative Example 4

[0064] Compared with Example 1, the difference between this comparative example is that the "benzoxazine sol" is replaced by the "water glass sol" and the immersion step in S4 is not performed. The specific implementation steps are:

[0065] S1. Adding water glass solution to phosphoric acid (wherein the volume ratio of phosphoric acid to water glass solution is 1:15-25; the water glass solution is diluted by water glass and deionized water in a volume ratio of 1:2-4) to obtain a slurry;

[0066] S2. After mixing 5 mL of a 3% aqueous solution of polyvinyl alcohol and 3 mL of a 35% aqueous solution of hydrogen peroxide, the mixture was slowly added dropwise to the slurry and stirred for 9 h to obtain a water glass sol;

[0067] S3. The density is 0.18g / cm 3The mullite fiber was impregnated into the sol under vacuum conditions for 1 hour, and cured in an inert gas atmosphere at 180°C for 2.5 hours to obtain a ceramic-based aerogel composite material precursor; the mixture was sealed and allowed to stand for 3 days, dried at 60°C for 24 hours, heated to 1100°C at a heating rate of 8°C / min and kept warm for 2 hours, and then cooled to room temperature to obtain a ceramic-based aerogel composite material.

[0068] The remaining raw materials and preparation process remain the same as in Example 1.

[0069] The performance of the ceramic-based aerogel composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was tested.

[0070] The results are shown in Table 1:

[0071] Table 1

[0072]

[0073]

[0074] It can be seen from Table 1 that the only difference between Examples 2-5 and Example 1 is the raw material ratio in the preparation method and the changes or modifications within a reasonable range. From the results, the thermal conductivity of the prepared ceramic-based aerogel composite material at 100°C is between 0.065-0.070 W / m·K; the compressive strength (5% strain) is in the range of 0.68-0.75 MPa; the shrinkage rate when heated at 800°C for 5 min is between 1.01%-1.18%; and the LOI is in the range of 32.4%-33.5%.

[0075] Compared with Example 1, since the ZrC xylene solution is in-situ ceramicized into ZrO2 under ultra-high temperature calcination, it can be closely attached to the ceramic-based aerogel composite material precursor, which greatly improves the thermal insulation and mechanical properties of the material. The results also prove this point. Compared with Example 1, the difference between Comparative Example 2 and Example 1 is whether mullite is added. Mullite fiber mainly acts as a framework in the material and can maintain the shape of the material at high temperature and under a certain pressure. Therefore, the mechanical properties of the composite material in Comparative Example 2 are reduced. Compared with Example 1, the results of Comparative Example 3 are that the thermal conductivity and The shrinkage rate increases and the limiting oxygen index decreases. This is because benzoxazine has inherent flame retardancy and heat resistance due to its rich benzene rings and nitrogen atoms in its structure. Therefore, it is more heat-resistant than general aerogel structures and has better flame retardancy. Compared with Comparative Examples 1-3, the significant decrease in the performance of the composite material in Comparative Example 4 shows that benzoxazine and ZrO2 have a synergistic effect. ZrO2 coated on the outer layer of benzoxazine solves the problem of uneven dispersion of ZrO2 and improves the thermal insulation and mechanical properties. Benzoxazine has inherent flame retardancy and heat resistance while reducing the problem of high brittleness of ceramic materials.

[0076] In summary, the present invention provides an ultra-high temperature ceramic-based aerogel composite material and a preparation method thereof. The prepared ceramic-based aerogel composite material has strong mechanical properties, good thermal insulation, heat resistance and flame retardancy, and has broad application prospects.

[0077] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An ultra-high temperature ceramic-based aerogel composite material, characterized in that: Including polybenzoxazine, mullite fiber and ZrO2; The polybenzoxazine and mullite fibers are cross-linked to obtain a ceramic-based aerogel composite material precursor; The ZrO2 is coated on the outer layer of the ceramic-based aerogel composite material precursor.

2. A method for preparing the ultra-high temperature ceramic-based aerogel composite material as claimed in claim 1, characterized in that: The following steps are involved: S1. After mixing benzoxazine, 4,4'-diaminodiphenylmethane and N,N-dimethylformamide, add oxalic acid DMF solution and stir for 1-2h to obtain a slurry; S2. After mixing the aqueous solution of polyvinyl alcohol and the aqueous solution of hydrogen peroxide, slowly dropwise add the mixture to the slurry and stir for 8-10 hours to obtain a sol; S3. impregnating the mullite fiber into the sol under vacuum conditions and curing to obtain a ceramic-based aerogel composite material precursor; S4. The aerogel composite material precursor is immersed in a mixed solution of ZrC and xylene under vacuum conditions, sealed and allowed to stand, dried, calcined, and cooled to room temperature to obtain a ceramic-based aerogel composite material.

3. The method for preparing an ultra-high temperature ceramic-based aerogel composite material according to claim 2, characterized in that: The oxalic acid concentration in the oxalic acid DMF solution is 7.15 mol / L, and the density of the mullite fiber is 0.15-0.2 g / cm 3 .

4. The method for preparing an ultra-high temperature ceramic-based aerogel composite material according to claim 2, characterized in that: The mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 2%-3%; the mass fraction of hydrogen peroxide in the hydrogen peroxide aqueous solution is 30%-35%.

5. The method for preparing an ultra-high temperature ceramic-based aerogel composite material according to claim 2, characterized in that: The mass fraction of ZrC in the mixed solution of ZrC and xylene is 2%-5%.

6. The method for preparing an ultra-high temperature ceramic-based aerogel composite material according to claim 2, characterized in that: The usage ratio of the benzoxazine, 4,4'-diaminodiphenylmethane, oxalic acid DMF solution, N,N-dimethylformamide, polyvinyl alcohol aqueous solution and hydrogen peroxide aqueous solution is 3-5g: 1-2g: 18-21mL: 25-35mL: 4-6mL: 2-4mL.

7. The method for preparing an ultra-high temperature ceramic-based aerogel composite material according to claim 2, characterized in that: The curing is carried out in an inert gas atmosphere at 150-200° C. for 2-3 hours.

8. The method for preparing an ultra-high temperature ceramic-based aerogel composite material according to claim 2, characterized in that: The immersion time is 0.5-1h; the sealing and standing time is 3-4d.

9. The method for preparing an ultra-high temperature ceramic-based aerogel composite material according to claim 2, characterized in that: The drying is carried out at 55-65° C. for 22-24 hours; and the calcining is carried out at a heating rate of 5-10° C. / min to a temperature of 1050-1150° C. and kept at that temperature for 1.5-2.5 hours.

Citation Information

Patent Citations

  • Preparation method of fiber-glass-reinforced TiO2-SiO2 composite aerogel heat-barrier material

    CN104261797A